Profile of Injured Singers: Expectations and Insights. (13th January 2022) - Childs, Lesley F.; Rao, Ashwin; Mau, Ted
Abstract : Objectives: To discover patterns of phonotraumatic lesions in singers and investigate factors that differentiate those who underwent surgery from those who did not. We hypothesized that 1) lesion type distribution differs by age, sex, singer classification (professional/amateur), and history of formal voice training; 2) the likelihood of surgery is associated with singer classification and voice training. Study Design: Retrospective. Methods: Retrospective review of 438 singers with phonotraumatic lesions over a 9‐year period. Lesion type distribution was analyzed with respect to sex, age, singer classification, and voice training. The association of eventual surgery with these factors was also analyzed. Results: Nodules accounted for over half of the cohort (58%), followed by pseudocysts (20%), polyps (14%), and cysts (4%). Nearly two of every three injured female singers, but fewer than one out of every three injured male singers, had nodules. In contrast, over half of the injured males had polyps, whereas only 6% of injured females had polyps. In females, polyps occurred at a later age, and in males, nodules occurred at a younger age compared to other lesion types. Only 14% of the total cohort eventually underwent surgery. Professional singers without formal voice training were almost eight times more likely to have undergone surgery than amateur singers with voice training. Conclusions: Professional singers were more likely to undergo surgery than amateurs, and formal voice training was associated with a lower likelihood of surgery. The observation that polyps tended to occur in older women may have implications for the pathogenesis of vocal fold polyps. Level of Evidence: 4 Laryngoscope, 132:2180–2186, 2022